2023
DOI: 10.1002/marc.202300036
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Surface Polymer Brushes Via Thin Film Crystallization and Solvent Annealing

Abstract: Polymer single crystals are used as templates to synthesize polymer brushes, known as the "polymer-single-crystal-assisted-grafting-to" (PSCAGT) approach. Polymer brushes with controlled grafting densities and spatial tethering locations are demonstrated. Previous works focused on solution crystallization, which involves large amounts of organic solvent, and the grafting density can only be tuned by varying crystallization temperatures. In this work, thin film crystallization is utilized to fabricate 2D polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The mismatch supramolecular interaction formed between rigid and flexible supramolecular fragments is used to realize the toughness of thermoplastic elastomers and thus improve their mechanical properties, but the synthesized elastomers become yellow due to the introduction of aromatic structure . So it can be concluded that the properties of polyurethane membranes can be improved by controlling several factors, such as intermolecular hydrogen bonds, molecular cross-linking structure, molecular weight, molecular structure symmetry, and so on. …”
Section: Introductionmentioning
confidence: 99%
“…The mismatch supramolecular interaction formed between rigid and flexible supramolecular fragments is used to realize the toughness of thermoplastic elastomers and thus improve their mechanical properties, but the synthesized elastomers become yellow due to the introduction of aromatic structure . So it can be concluded that the properties of polyurethane membranes can be improved by controlling several factors, such as intermolecular hydrogen bonds, molecular cross-linking structure, molecular weight, molecular structure symmetry, and so on. …”
Section: Introductionmentioning
confidence: 99%